Building Climate-resilient Infrastructure through Microorganisms: A Mini Review - Qureshi, Muhammad Naqeeb Ur Rehman; Javaid, Muhammad Jahanzaib; Kanwal, Maria; Rasool, Atta; Qureshi, Muhammad Anees Ur Rehman (BioScientific Review, 2025)
Microorganisms were considered as the disease-causing agents a long time ago. However, this fear transformed into their acceptance due to their biological, physiological, and ecological understanding which resulted in the modification of Germ Theory. Currently, mutualistic and parasitic role of microbes is well-understood which paved the path for their biotechnological use. Additionally, microbial bio-coatings are outstanding bio-sensors for environmental monitoring, food analysis, heavy metal detection, and bioelectronics. The use of bacteria in self-healing concrete repair is advantageous due to their potential for low-cost binding, providing strength, stiffness, durability, and reduction in steel reinforcements. The surface membrane of bacteria is negatively charged which binds with metallic ions in basic medium that is a key factor in carbonate precipitation on their surfaces to repair cracks. On the other hand, calcite precipitation also influences the life span and stability of concrete. Recently, microorganisms assisted remediation, geo-polymerizations, and carbon capture. Furthermore, heavy metal detections were reported which may revolutionize microbial utilization in building climate resilient infrastructure. The current review spotlighted the applications of microorganisms in concretes, soil engineering, bio-coatings, bio-remediation, carbon capturing, and monitoring soil properties. In the end, recent developments and future directions were meticulously-vetted. The study concluded that the application of microbes in building climate-resilient infrastructure is reliable to decrease carbon emissions, enhancing self-repair concrete systems and developing sustainable green systems. Exploitation of natural phenomenon occurring in microorganisms not only aids in more climate resilient systems but also contributes positively for a green environment.